Non-traumatic scapholunate dissociation in a 10-year-old female: A case report - Bandinelli, Diletta; Pagnotta, Alessia; Pieracci, Edoardo Maria; Basiglini, Luca; Aulisa, Angelo Gabriele (Frontiers in Surgery, 2022)
Introduction Severe or minor repetitive trauma, inflammation, infection, tumors, and congenital ligamentous laxity have been etiologically implicated in scapholunate dissociation (SLD). While a few cases of asymptomatic SLD have been reported in litterature: despite radiographically demonstrated widened scapholunate angles and rotatory subluxation of the scaphoid, these patients had mild or no pain and no dorsal intercalated segment instability deformity. We have reported a case of a monolateral non-traumatic SLD in a young 10-year-old girl that led to an important range of motion impairment with no wrist pain. The case represents a rarity for no previous trauma, young age and no pain. Main symptoms and important clinical findings In our patient the examination relevated reduced range of motion in left wirst, no pain during passive or active mobilization. The X-ray showed a 16 mm scapholunate gap in anteroposterior roentgenogram. In this case we suggested that congenital or developmental ligamentous laxity may be the SLD cause. The diagnostic assessment was completed with a wirst MRI and CT. Therapeutic interventions and outcomes The patient underwent open dorsal surgery: we directly reduced dislocated bones and fixed them with five percutaneous 1 mm-k-wires. Finally the scapholunate ligaments were repaired using bone absorbable anchor sutures. The wrist was immobilizated in a volar cast for 8 weeks. Patient returned to her daily life activities (included sport) within 12 months. Conclusion Carpus injuries are rare in children and treatment at this age is controversial. Our case demonstrates that the patient has had a good outcome. The physio-rehabilitation has been long. Most studies showed excellent clinical results after an average of 2.4 years.